(untitled) (Research, Society and Development, 2022)
The objective was to identify UI as a factor associated with decreased QoL in climacteric women, and it became relevant to support strategies aimed at promoting health, relieving symptoms, preventing and controlling UI. And in this way, improve the QOL of these women with an inclusive, holistic and humanized approach. The final sample of this review consisted of nine articles dated between 1998 and 2021. In the selection of the materials used, the results obtained in the characterization of the scientific production on the forms of evaluation of the strength of the pelvic floor muscles and techniques of strengthening this, in women with UI. The current review showed that the publications carried out in this area, and especially by nurses, still have little representation, and that due to the relevance of the topic we need to develop other studies showing the relevance of the nurse’s work, in the act of the nursing consultation and its legal support., evaluating the strength of the pelvic floor muscles, and if there is a detection of muscle weakness, start the guidance on the importance of muscle strengthening in the support and continence of Organs pelvic organs, in addition to guiding that this strengthening. Advise that it should be a supervised activity with the proper guidelines during consultations and in focus groups, in order to improve the QOL of the female population in general, with easy information, which convey security to women and encourage this treatment that allows maintaining the routine and social life of women.